(untitled) (The Journal of Modern Project Management, 2023)
This article includes a detailed study with the objective to investigate the variables and effects associated with delays in urban development projects within Binh Duong Province, Vietnam. The research methodology employed in this study encompassed the administration of surveys to a sample size consisting of 486 experts and experienced firms. This approach was complemented by extensive literature reviews and the use of comprehensive questionnaires. The evaluation of project effectiveness involved the utilization of advanced data analysis tools, namely the Relative Importance Index (RII), Net Present Value (NPV), and Cost-Benefit ratio (B/C). The study’s findings elucidate five notable variables that lead to project delays in Binh Duong Province: The discussion pertains to the unsuitable nature of the plans, the managerial capabilities, financial aspects, human resource considerations, and the intricate nature of the projects. The previously mentioned standards have been recognized as crucial elements necessitating focused efforts and enhancements in order to optimize project efficiency and mitigate delays. The study also emphasizes the financial ramifications of building delays on firms in the industry. More specifically, the findings suggest that delays accounting for 15% to 39% of the overall duration of civil projects and 8% to 39% of the overall duration of traffic projects can lead to significant financial losses for contractors. The results of this study highlight the importance for construction companies to carefully evaluate the effectiveness of their investments by considering the significant effects of delays. This will allow them to make well-informed choices when selecting projects. In all aspects, this study offers valuable insights into the various elements that exert influence on the occurrence of delays in urban development projects within Binh Duong Province. By comprehending these characteristics and their ramifications, contractors and stakeholders are able to employ efficacious tactics to alleviate delays, optimize project management methodologies, and choose appropriate projects that guarantee investment efficiency.